Television beyond digitalization: Economics, competitiveness and future perspectives. (1st June 2018) - Maniou, Theodora A.; Seitanidis, Ioannis
In an unstable and fragmented global media environment, beset by an economic crisis and technological changes, the future of traditional television seems bleak and uncertain. The age of digitalization brought a series of challenges for non-linear broadcast entities, underlining a pressing need for content reassessment and market restructuring. This study examines the competitiveness of traditional television in contrast to other media (new and traditional), as well as the future of television in a period when digital media seem to dominate the sociopolitical-economic environment, while traditional media seem to be in their death throes. The primary aim of this study is to investigate whether post-broadcast television can preserve its audience and survive in an era beyond digitalization. Cyprus was selected as a case study for this research since, after 2013, the country suffered an unprecedented economic and banking crisis that led to significant changes within the country's media sector and especially television.